Fotometric method to determine yeast flocculation caused by Lactobacillus fermentum in alcoholic fermentation process - Castro e Souza, Marco Antonio de [UNESP]; Rossini Mutton, Marcia Justino [UNESP] (Univ Federal Lavras-ufla, 2004)
In the production of alcohol by yeast fermentation, flocculation is a natural mechanism of cell aggregation. This mechanism can be induced by several factors, as the interaction with flocculent bacteria like Lactobacillus fermentum which strongly interacts with yeasts. Flocculation means loss to the process because both the mills that recover cells by centrifugation systems and the mills that do not use this system endure excessive yeast loss, as consequence of operational problems because of the flocculation, being the industrial performance sometimes seriously compromised. The present research evaluated the flocculation in fermented wine under two fermentation temperatures and pH's used in treating yeasts, but no statistical difference was found between them. This study also evaluated the dispersion capacity of flakes in three pH conditions for treating yeasts in the industry stage, showing highly significant differences among such conditions. The highest dispersion capacity in treating yeasts is desirable to control industrial flocculation. These evaluations were possible through the usual technique to determine flocculation, modified by the previous de-flocculation of samples, which was responsible for higher stability in spectrophotometer readings.
Keywords: Floculent bacteria; acid dispersion; experimental fermentation; acid treatment; industrial yeast; espectrofotometry